Pengembangan dan validasi awal kuesioner untuk menilai pusat kebugaran - Santos, Michael (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
This manuscript comprehensively examines the development and preliminary validation of a questionnaire designed to assess fitness centers. The study aims to address existing gaps in the literature by providing a standardized tool for evaluating the quality of fitness facilities. The study aims to design, validate, and present a preliminary assessment instrument tailored specifically for fitness centers, encompassing various aspects such as program offerings, facility conditions, and staff competencies. The research methods involved the identification of key indicators affecting fitness center services, followed by the generation and validation of questionnaire items through a rigorous statistical analysis. The research subjects consisted of 119 fitness enthusiasts from Angeles City, Philippines, who actively participated in the validation process. The instruments used in data processing included Likert-style rating scales and statistical methods such as Point Biserial Correlation and t-tests. The analysis of data utilized in data processing led to the retention of 59 questionnaire items, demonstrating significant correlation coefficients. The study's results highlight the reliability and validity of the developed questionnaire as a valuable tool for assessing fitness centers, providing insights into client needs and areas for improvement. In conclusion, the preliminary validation of the questionnaire serves as a crucial step towards enhancing the quality and standards of fitness center services, benefiting both managers and regulatory authorities in ensuring the provision of safe and effective fitness facilities.